Association of systemic immune-inflammation index with type 2 diabetes mellitus and its prognostic significance: a systematic review and meta-analysis - Xu, Ru; Jiang, Lele (Frontiers in Endocrinology, 2025)
BackgroundThe systemic immune-inflammation index (SII), a novel biomarker, may be associated with type 2 diabetes mellitus (T2DM). This study aimed to investigate the relationship between SII and T2DM, as well as its prognostic value.MethodsA comprehensive search of PubMed, Embase, Cochrane Library, Web of Science, CNKI, VIP, Wanfang, and Biomedical Literature Database was conducted to identify eligible studies published up to October 26, 2024. Relative risk (RR), odds ratio (OR), and hazard ratio (HR), along with their 95% confidence intervals (CIs), were extracted and synthesized. Statistical analyses were performed using Stata 15.1 software.Results21 studies were included. SII was associated with an increased risk of major adverse cardiovascular events (MACE) and mortality. Each one-unit standard deviation (SD) increase in SII was positively correlated with MACE risk (OR/HR = 1.07; 95% CI: 1.04-1.10; P < 0.001). However, no significant association was found between SII and diabetic retinopathy. Regarding glucose metabolism abnormalities and diabetic nephropathy, high SII was significantly associated with increased risk (P < 0.05).ConclusionsElevated SII is associated with an increased risk of MACE, mortality, diabetic nephropathy and glucose metabolism abnormalities but shows no significant correlation with diabetic retinopathy.